ORAL ARIPIPRAZOLE FOR THE TREATMENT OF TOURETTE'S SYNDROME IN CHILDREN - Frilya Rachma Putri; Mayniar Ayu Rahmadianti (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
Background Among the pharmacotherapy recommendations for Tourette syndrome (TS), Aripiprazole is a potential treatment option for TS and a relatively safe alternative in the pediatric population. Case presentationWe report the case of a pediatric patient with TS who was admitted to the hospital after demonstrating severe involuntary movements. The symptoms emerged early in childhood and remained subclinical. It became more noticeable at 3 months before admission when the frequency and the severity started to increase progressively reaching its peak at one month before hospitalization. From further assessment, we found speech delay and a notably high score of Strength and Difficulties Questionnaire (SDQ)At the time of hospitalization, the symptom relieved following the admission of Aripiprazole 1 x 2 mg. It significantly diminished to infrequent minor facial tics. There was no adverse effect reported upon hospital discharge. We also performed family psychoeducation and speech therapy as adjuvant therapy.ConclusionsWe selected Aripiprazole because of its unique mechanism of action resulted in a dopamine stabilizer feature with less side effect. The most common ones are nausea, sedation, and increased appetite where, generally, are lessen within 2 weeks. Moreover, in contrast with other antipsychotics, Aripiprazole would not provoke hyperprolactinemia. The more severe side effect such as extrapyramidal symptoms and weight gain are usually dose-dependent at around 10 mg/day. Aripiprazole is also favourable, especially for refractory cases.